Identify the professional pressures of physical education teachers and their impact on the level of lesson in secondary schools in Maysan governorate - Qasim Kadhim AL-Shareefi, Maytham (International Journal of Psychosocial Rehabilitation, 2020)
One of the most important factors for improving performance in most jobs and businesses is to raise or reduce pressure on workers in all fields, including the field of work sport, especially in the field of teaching, which is required to deal with the relatively large numbers of students. Our country, which has greatly reduced the interest in studying physical education, has put great pressure on teachers and even students themselves. Which provides for the type of rice, the importance of research according to personality and professional pressures by the teacher, and attention to their opinions and to identify the real suffering that is an obstacle to their job performance in order to work to achieve it and to develop effective solutions to that? In a problem, the researcher emphasized that professional pressures are not limited to a specific profession or work per se, but rather because of the multiplicity of professions and jobs, and the teaching profession is one of the professions that cause many pressures, such as the result of the many duties and burdens placed on the shoulders of the teacher in the various stages of study, including the secondary stage The professional pressures in which we try to answer the following questions range1. What are the factors that cause professional pressure on the secondary school physical education teacher?2. What are the factors and causes of professional stress that affect the physical education teacher in secondary schools?3. Is there a relationship between the factors causing occupational stress that physical education teachers are exposed to?The research aims to identify the professional pressures of physical education teachers in secondary schools in Maysan governorate, as well as to identify the factors most influencing the professional impact on school education sports in secondary schools in Maysan governorate. As well as identifying the relationship between the factors causing professional pressure on physical education teachers in secondary schools in Maysan Governorate. As well as knowing the effect of professional pressure on the level of education in physical education in secondary schools in Maysan governorate, while the main hypotheses are that there is professional pressure on sports research on physical education teachers in secondary schools. To Maysan Governorate, where I assumed that there are among the various factors that cause professional pressure on physical education teachers in secondary schools in Maysan Governorate. In the third topic, the researcher's community and the research sample were deliberately represented in the category of physical education in schools and high schools due to the emergence of al-Mahfat and 64 teachers from Maysan, while the researcher followed the descriptive approach to survey the curriculum. According to the relevance and nature of the research in the fourth chapter, the results of the research were presented, analyzed, and discussed through the statistical processes that were conducted on the research results. As for the fifth topic, it included automatic conclusions and recommendations represented in the presence of educational, financial, and social pressures and negative social impacts on physical education teachers in secondary schools in the governorate, while the trend of most schools was noted. High school students' studying physical education increases the rate of professional pressure on physical education teachers in those schools. Note that the lack of gyms, stadiums, and sports facilities is  causing significant pressure on teachers. The researcher also found that the professional pressures faced by the physical education teacher negatively affect the implementation of the physical education lesson.